Frgs top-down novel advanced organic materials: polyimides (pi) & poly (p-phenylenevinylene) (ppv) project 1: syntheses of new polymeric materials - Hamzah, Ahmad Sazali; Shaameri, Zurina; Muhammat, Mohd Fazli; Jumali, Nor Saliyana (2010)
This research involved the synthesis of polyimides (PI) and poly(p-phenylenevinylene) (PPV) derivatives. Polyimide was synthesized through condensation reaction which involved the reaction between variety diamines and dianhydrides with different substitution. The synthetic approaches involved the formation of poly(amic acid) (PAA) precursors followed by the conversion of PAA acids to desired polyimides via thermal imidization process. Six new polyimides were successfully synthesized. All synthesized polyimides were characterized by FTIR spectroscopy, viscosity, solubility and thermal analysis. Poly(p-phenylenevinylene) (PPV) derivatives was successfully synthesized via modified Gilch's route. The PPV derivatives were prepared by chemically modifying the PPV unit at 1 and 4 positions of the aromatic ring with different alkyl chain lengths. Ten new PPVs and MEHPPV which is a commercially available polymer were successfully synthesized using this method. Seven of which were further subjected to conductivity measurement against MEH-PPV as the standard, to observe the effect of the modification of the ring system. The results showed that one of PPV derivative has higher conductivity in comparison to MEH-PPV, 1.02 X 10-7 Scm-I. The highest conductivity value was recorded for polymer 36 (MPR-PPV) which is 1.11 X 10-6 Scm-I. In conclusion, 10 new PPY derivatives were successfully synthesized in three main steps and some of these polymeric materials showed good conductivity in their free standing condition. These PPY derivatives can thus provide an option and good candidates for several applications including polymer light emitting diodes (PLEDs), photovoltaic cells, photodiodes, solar cells and optically pump-lasers.